Macroeconomic Cycles in China - Oppers, S. (Washington, D.C. : International Monetary Fund, 1997)
This paper investigates the macroeconomic cycles China has experienced since the onset of reform in the late 1970s. It finds that the recurrent inflationary episodes that characterize the cycles are associated primarily with surges in the main components of aggregate demand. The most recent cycle stands out in achieving for the first time a reduction in inflation without a major slowdown in growth. The soft landing was facilitated by a number of factors, including increases in capacity as a result of the surge in investment spending early on in the cycle.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet